2003
DOI: 10.1073/pnas.0236979100
|View full text |Cite
|
Sign up to set email alerts
|

Impaired B cell development and function in mice with a targeted disruption of the homeobox gene Hex

Abstract: Hex is a homeobox gene that is expressed in all stages of B cell development except plasma cells. We studied lymphocyte development in the absence of Hex by using the RAG1-deficient blastocyst complementation system because homozygous disruption of Hex is embryonic lethal. Hex ؊/؊ ;RAG1 ؊/؊ chimeric mice had severely reduced numbers of mature B cells, pre-B cells, and CD5 ؉ B cells with a striking 15-fold increase in the percentage of B220 ؊ CD19 ؉ cells in the bone marrow. Hex ؊/؊ ;RAG1 ؊/؊ chimeric mice fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 21 publications
3
45
0
1
Order By: Relevance
“…Hhex-deficient mice have multiple developmental defects, including marked abnormalities of heart and vascular development To determine the function of Hhex in vivo, we generated a null allele using a targeting construct designed to delete exons 1 and 2 of the Hhex genomic sequence, which removed the transcription start site, translational start site and most of the homeobox as previously described (Bogue et al, 2003). Homozygous deletion of Hhex results in embryonic lethality, as evidenced by the fact that we have detected no live born Hhex -/-mice and that the ratio of Hhex…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hhex-deficient mice have multiple developmental defects, including marked abnormalities of heart and vascular development To determine the function of Hhex in vivo, we generated a null allele using a targeting construct designed to delete exons 1 and 2 of the Hhex genomic sequence, which removed the transcription start site, translational start site and most of the homeobox as previously described (Bogue et al, 2003). Homozygous deletion of Hhex results in embryonic lethality, as evidenced by the fact that we have detected no live born Hhex -/-mice and that the ratio of Hhex…”
Section: Resultsmentioning
confidence: 99%
“…The Hhex targeting construct and heterozygous ES cells were generated as previously described (Bogue et al, 2003). Two heterozygous clones were injected into C57BL/6J blastocysts to generate chimeric mice.…”
Section: Generation Of Hhex -/-Micementioning
confidence: 99%
See 1 more Smart Citation
“…Hex expression is downregulated during terminal differentiation of B cells, suggesting that Hex is involved in B-cell development (Manfioletti et al, 1995). Mice generated from chimeric blastocysts composed of HexÀ/À and RAGÀ/À ES cells are defective in normal B-cell development and function but have normal T-cell differentiation (Bogue et al, 2003). Recently, it has been demonstrated that transgene-driven expression of Hex in thymocytes disrupts normal T-cell development, resulting in fewer double-positive and more CD8 þ cells in the thymus and decreased numbers of T cells in the periphery (Mack et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the embryonic lethality of Hhex and investigate its role in hematopoietic development, blastocyst complementation and embryoid body differentiation approaches have been used. Using blastocyst compensation of Rag1 2/2 mice, it has been shown that Hhex is required for B-cell development and function, 16 whereas, in embryonic stem cell differentiation models, Hhex is required for maturation and proliferation of definitive HSCs. [17][18][19] Thus, Hhex is postulated to play a role in hematopoietic differentiation and stem cell self-renewal in the adult.…”
Section: Introductionmentioning
confidence: 99%